Evaluation of an Adenoviral Vector Encoding Full-Length Human Factor VIII in Hemophiliac Mice - Connelly, Sheila; Andrews, Julie L.; Gallo-Penn, Angela M.; Tagliavacca, Luigina; Kaufman, Randal J.; Kaleko, Michael (Thrombosis and Haemostasis, 1999)
Adenoviral vectors provide a promising gene therapy system for the treatment of hemophilia A. Potent vectors encoding a human factor VIII (FVIII) cDNA were developed that mediated sustained FVIII expression in normal and hemophiliac mice and complete phenotypic correction of the bleeding disorder in hemophiliac mice and dogs (Connelly and Kaleko, Haemophilia 1998; 4: 380-8). However, these studies utilized vectors encoding a truncated version of the human FVIII cDNA lacking the B-domain (BDD FVIII). In this work, an adenoviral vector encoding the human full-length (FL) FVIII cDNA was generated and characterized. While functional FL FVIII was secreted in vitro, expression of the FL protein was not detected in the plasma of vector-treated hemophiliac mice. Unexpectedly, the FL FVIII vector-treated animals demonstrated phenotypic correction of the bleeding defect as measured by a tail-clip survival study. FL FVIII protein was visualized in the mouse livers using human FVIII-specific immunohistochemical analyses. These data demonstrate that adenoviral vector-mediated in vivo expression of BDD FVIII is more efficient than that of the FL protein and that phenotypic correction can occur in the absence of detectable levels of FVIII.